Rapid PCR detection of group a streptococcus from flocked throat swabs: A retrospective clinical study - Tam Ronald; Barrowman Nicholas; Moldovan Ioana; Rajakumar Derek; Goldfarb David; Slinger Robert; Chan Francis (BMC, 2011)
Abstract Background Rapid diagnosis of GAS pharyngitis may improve patient care by ensuring that patients with GAS pharyngitis are treated quickly and also avoiding unnecessary use of antibiotics in those without GAS infection. Very few molecular methods for detection of GAS in clinical throat swab specimens have been described. Methods We performed a study of a laboratory-developed internally-controlled rapid Group A streptococcus (GAS) PCR assay using flocked swab throat specimens. We compared the GAS PCR assay to GAS culture results using a collection of archived throat swab samples obtained during a study comparing the performance of conventional and flocked throat swabs. Results The sensitivity of the GAS PCR assay as compared to the reference standard was 96.0% (95% CI 90.1% to 98.4%), specificity 98.6% (95% CI 95.8% to 99.5%), positive predictive value (PPV) 96.9% (95% CI 91.4% to 99.0%) and negative predictive value (NPV) of 98.1% (95% CI 95.2% to 99.2%). For conventional swab cultures, sensitivity was 96.0% (95% CI 90.1% to 98.4%), specificity 100% (95% CI 98.2% to 100%), PPV 100%, (95% CI 96.1% to 100%) and NPV 98.1% (95% CI 95.2% to 99.3%) Conclusions In this retrospective study, the GAS PCR assay appeared to perform as well as conventional throat swab culture, the current standard of practice. Since the GAS PCR assay, including DNA extraction, can be performed in approximately 1 hour, prospective studies of this assay are warranted to evaluate the clinical impact of the assay on management of patients with pharyngitis.